HW6sol - tion to each other. The only place that can go...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
M408C, Homework 6 — Solution Instructor: Guoliang Wu 1. Find the absolute maximum and absolute minimum of the function f ( x ) = x p 4 - x 2 , on [ - 1 , 2] . Solution. f 0 ( x ) = p 4 - x 2 + x - 2 x 2 4 - x 2 = 4 - 2 x 2 4 - x 2 So f 0 ( x ) = 0 4 - 2 x 2 = 0 x 2 = 2 x = ± 2 . Note that - 2 - 1 . 414 is not in [ - 1 , 2]. So 2 is the only critical point. We evaluate f at 2 , - 1 and 2, f ( 2) = 2 p (4 - 2) = 2 , f ( - 1) = - 3 , f (2) = 0 . So the absolute maximum is f ( 2) = 2 and the absolute minimum is f ( - 1) = - 3. 2. Let f ( x ) = x + 1 - x 2 - 1 for x 0. The following sequence of questions will help you to understand why f ( x ) < 0 (equivalently, x + 1 < x 2 + 1) for all x > 0. (a) Assume (for the sake of contradiction) that f ( b ) 0 at some point b > 0. What can you say about the sign of the value f ( b ) - f (0) b - 0 ? (b) Can you apply the Mean Value Theorem to f ( x ) on [0 ,b ]? Why? And what can you conclude from it, assuming f ( b ) 0? (c) Now compute the derivative f 0 ( x ) = d dx ( x + 1 - x 2 - 1). What can you say about the sign of this derivative? In view of (a)–(c) above, you should get conclusions that are in contradic-
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: tion to each other. The only place that can go wrong the assumption that f ( b ) ≥ 0 at some point b > 0. Therefore, f ( x ) < 0 for all x > 0. (This argument is called “proof by contradiction”.) Solution. (a) Since we assume f ( b ) ≥ , f ( b )-f (0) b-= f ( b ) b ≥ . 1 (b) Since the function f ( x ) is continuous on [0 ,b ] and differentiable on (0 ,b ), we can apply the MVT. From MVT, we conclude that there exists c in (0 ,b ) such that f ( c ) = f ( b )-f (0) b-= f ( b ) b ≥ (c) f ( x ) = 1 2 √ x +1-1 2 = 2(1-√ x +1) 2 √ x +1 < , for x > 0. But f ( c ) ≥ 0 from (b), where c in (0 ,b ), so we have a contradiction. 2...
View Full Document

This note was uploaded on 12/03/2010 for the course M 408c taught by Professor Mcadam during the Fall '06 term at University of Texas at Austin.

Page1 / 2

HW6sol - tion to each other. The only place that can go...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online